Peran Teknologi dalam Optimalisasi Pengelolaan Zakat untuk Pemberdayaan Ekonomi - Candra, Jeki; Nasution, Yenni Samri Juliati (Polyscopia, 2025)
This study explores the role of technology in optimizing zakat management for the economic empowerment of the Muslim community. As an essential instrument in Islamic economics, zakat holds significant potential in poverty alleviation and enhancing societal welfare. However, conventional zakat management often faces challenges such as a lack of transparency, accountability, and distribution efficiency. In the digital era, technology offers strategic solutions through innovations such as digital platforms, blockchain-based applications, big data analytics, and electronic payment systems. This study employs a qualitative approach with a literature review method to analyze the implementation of technology in zakat management across various zakat institutions. The findings indicate that technology enhances the efficiency of zakat collection, expands the reach of muzakki (donors), and ensures a more targeted distribution to mustahik (recipients). Furthermore, technology fosters transparency and strengthens public trust in zakat management institutions. Thus, integrating technology into zakat management not only reinforces zakat’s role as a social finance instrument but also serves as a catalyst for the sustainable economic empowerment of the Muslim community.